Serving the users of cultural institutions in the digital era : questions to be answered, decisions to be taken - Horvat, Aleksandra knjižničarka (Array, 2013)
National teams of students who participated in 2012 Erasmus Intensive Program ’Library, Information and Cultural Management – Academic Summer School’ were asked to do researches on public libraries on Facebook in their countries. In the paper some of the results are presented and discussed.